2012
DOI: 10.1172/jci44927
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of thioredoxin-interacting protein in mice impairs mitochondrial function but protects the myocardium from ischemia-reperfusion injury

Abstract: Classic therapeutics for ischemic heart disease are less effective in individuals with the metabolic syndrome. As the prevalence of the metabolic syndrome is increasing, better understanding of cardiac metabolism is needed to identify potential new targets for therapeutic intervention. Thioredoxin-interacting protein (Txnip) is a regulator of metabolism and an inhibitor of the antioxidant thioredoxins, but little is known about its roles in the myocardium. We examined hearts from Txnip-KO mice by polony multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
136
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(150 citation statements)
references
References 57 publications
(67 reference statements)
14
136
0
Order By: Relevance
“…Hypoxia/Reoxygenation-One adaptive mechanism employed to protect cells from harmful ROS is through regulation of mitochondrial oxidative phosphorylation that generates ROS as a byproduct (24). We analyzed mitochondrial oxygen consumption rate (OCR) using the Seahorse extracellular flux analyzer and confirmed that the OCR in WT cells was reduced after hypoxia/reoxygenation, as expected (Fig.…”
Section: Caspase 1 Deficiency Results In Impaired Mitochondrial Clearsupporting
confidence: 74%
See 1 more Smart Citation
“…Hypoxia/Reoxygenation-One adaptive mechanism employed to protect cells from harmful ROS is through regulation of mitochondrial oxidative phosphorylation that generates ROS as a byproduct (24). We analyzed mitochondrial oxygen consumption rate (OCR) using the Seahorse extracellular flux analyzer and confirmed that the OCR in WT cells was reduced after hypoxia/reoxygenation, as expected (Fig.…”
Section: Caspase 1 Deficiency Results In Impaired Mitochondrial Clearsupporting
confidence: 74%
“…The inhibition of mitochondrial respiration during hypoxia/ hemorrhagic shock and the removal of mitochondria to reduce ROS production upon reoxygenation may confer protection against mitochondrial dysfunction and subsequent cell death (10,24) and is a major cellular adaptive response to hypoxia. Although low levels of ROS may be critical to signaling in cell stress and preconditioning responses (38), our study suggests that high levels of mitochondrial ROS contribute directly to hepatocyte cell death during hypoxia/reoxygenation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] We and others have implicated TxNIP in this initiating event. In cardiomyocytes 38 and mesangial cells from TxNIP-deficient mice, 15 decreased mitochondrial glucose metabolism concomitant with increased glycolysis and lactate production has been observed. Furthermore, HG did not stimulate mesangial cell mitochondrial membrane potential or ROS generation in the TxNIP-deficient state, while adenoviral mediated overexpression of TxNIP restored these responses.…”
Section: Discussionmentioning
confidence: 95%
“…15,38 Evidence for a defect in ROS generation in vivo was manifested by the lack of increase in urinary 8-OHdG in the TxNIP 2/2 diabetic mice in contrast to diabetic WT ( Figure 5B). This was supported by the reduced mitochondrial membrane potential and ROS production in TxNIP-silenced cultured podocytes exposed to HG (Figure 7, A-C).…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported CD47-dependent expression of thioredoxin-interacting protein (TXNIP), and TXNIP was upregulated by treatment with the CD47 antibody B6H12 in triple negative breast cancer stem cells (109). In part by inhibiting the antioxidant function of thioredoxin-2 (Trx2) in the mitochondria, TXNIP limits resistance to oxidative stress, and deletion of TXNIP-protected mice from ischemia-reperfusion injury (308,309). Further studies are needed to test the hypothesis that CD47-mediated upregulation of TXNIP in cancer stem cells could sensitize them to the oxidative stress caused by radiation or anthracyclines.…”
Section: A Redox Signaling In Stem Cellsmentioning
confidence: 95%